From the history of teaching Russian language and literature at the old Vilnius University - Kaupuža, A. (Literatūra, 1969)
The biography as well as activities of the Russian philologist Professor I. N. Cherniavsky at the Vilnius University in the beginning of the 19th century have been little investigated. A close study of the material found in archives enabled the author to present a general idea about his lectures and to restore some biographical facts. The investigation of university syllabi and examination questions resulted in the following: the information, communicated by I. N. Cherniavsky, was extensive, he was a man of great learning in his field and was a warm propagandist of Russian literature and culture.